Post-divorce Child Care to Ensure the Children welfare : A Perspective of Islamic Family Law - Fatimawali Fatimawali (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2026)
Child care (nafaqah) after divorce often faces implementation challenges despite being a continuous legal and religious obligation. This qualitative study with a normative–empirical approach investigates the essence, implementation, and influencing factors of post-divorce parental responsibility for child maintenance in Palu City. Data were gathered through in-depth interviews with judges, lawyers, religious leaders, and affected families, alongside field observations and documentation. The findings reveal that child maintenance is a divine trust (amanah) linked to lineage (nasab) that persists regardless of marital dissolution. However, its implementation in Palu City remains suboptimal; maintenance is frequently irregular or discontinued due to post-divorce conflict, economic constraints, low legal awareness, and weak court enforcement. Consequently, the financial burden shifts to mothers, causing economic and psychological vulnerability for the children.